2016
DOI: 10.1176/appi.ps.201400295
|View full text |Cite
|
Sign up to set email alerts
|

Organized Self-Management Support Services for Chronic Depressive Symptoms: A Randomized Controlled Trial

Abstract: These findings support providing regular outreach care management and a self-care group offering a combined behavioral and recovery-oriented approach for people with chronic or recurrent depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(64 citation statements)
references
References 59 publications
0
64
0
Order By: Relevance
“…The follow-up period was longer in the ZemCAD intervention. Ludman et al [39] focused on patients with chronic depression, but had a longer, more intensive treatment than the ZemCAD intervention. All three studies had group settings and a peer support component was present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The follow-up period was longer in the ZemCAD intervention. Ludman et al [39] focused on patients with chronic depression, but had a longer, more intensive treatment than the ZemCAD intervention. All three studies had group settings and a peer support component was present.…”
Section: Discussionmentioning
confidence: 99%
“…Groups enable patients to better withstand alienation and crisis because of the connectedness and social support [42]. Peer support is proven to be supplementary in various self-management programs [38, 39, 43]. Interactions with peers may enhance patients’ belief in their own ability to self-manage their lives, thus increasing perceptions of recovery and lowering feelings of anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…There is wide interest in encouraging self-management due to its potential to improve patient engagement in care and health outcomes for chronic conditions, 52 including HIV 53 and depression. 9 Promoting self-management may also reduce costs on the health care system. 54 However, supporting patient self-management can be difficult in safety-net settings 55 and in HIV care, 53 especially when patients are living with multiple chronic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A range of evidence-based treatment options exist for depression, including medications, group therapy, cognitive behavioral therapy, and self-management support. 79 Depression treatment is associated with improved adherence to antiretroviral therapy 10 and better health outcomes for depression and HIV, 11,12 yet many PLWH in need of mental health care remain untreated or undertreated for depression. 13 Similar to the HIV care cascade, which outlines the steps from HIV diagnosis to viral load suppression, 14 the “depression treatment cascade” depicts the stages from clinical recognition of depression to treatment initiation and, ultimately, remission of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary analysis of data from a randomized controlled trial of a self-management support services intervention for chronic depression was used. 9 The randomized trial showed the intervention improved the total RAS score and reduced depressive symptoms and major depressive episodes. For this study, we examined both factor structure and sensitivity to change of the RAS.…”
Section: Introductionmentioning
confidence: 99%